I limiti all’esercizio del culto nell’emergenza sanitaria e la ‘responsabile’ collaborazione con le confessioni religiose (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Le restrizioni introdotte dalla normativa ‘emergenziale’ - 2. La legittimità delle restrizioni sotto il profilo del bilanciamento tra interessi - 3. (segue) e del rispetto del principio pattizio - 4. I protocolli per la ripresa delle funzioni religiose come strumenti di ‘responsabile’ collaborazione - 5. I profili di criticità - 6. Conclusioni.The Limits to the Practice of Worship during the Health Emergency and the ‘Responsible’ Collaboration with the Religious DenominationsABSTRACT: The severe pandemic which has affected the Italian country (as well as the rest of the world) led the Government to introduce restrictive measures whose aim was to hinder the diffusion of the virus. Such measures imposed a general prohibition to any movements and gatherings, thus affecting the exercise of many fundamental rights and, among these, the freedom of worship, considered in its interpersonal dimension. In particular, as far as this right was concerned, the legitimacy of its restriction had to be assessed not only in the light of its balance with other competing interests (namely, public health), but even of the constitutional principle which compels the State to regulate its relationships with the religious denominations on the base of agreements signed whith their representatives (art. 7, c. 2, and 8, c. 3, Cost.). For these reasons, some scholars criticized the unilateral nature of the restrictive measures, whilst they welcomed favorably the signing of the ‘health protocols’ adopted in order to restart the celebration of public worship ceremonies. This paper aims at assessing whether a unilateral limitation of the freedom of worship might be considered legitimate. In addition, it is going to investigate the juridical nature of the abovementioned health protocols, in order to highlight any critical profiles.